Beiträge zur Geschichte des antiken Glases. XIII. Nuzi-Perlen. Ein Versuch - Haevernick, Thea Elisabeth (1967)
12. Jahrgang, 1965; Mykenae, Boğazköy, Djonii, Aghla-Evlar, Shah Tepe, Tarkalan, Nuzi, Assur, Susa, Nippur, Açana, Byblos, Hazor, Tell Abu Hawam, Megiddo, Beth Shan, Gezer, Lachish.